(3eLehY COHjs - (3eLghds
(3ChdgG (B:s
(3ddbGVj aNQ GdOjf Hf ecGfS QMeg Gddg CfYe UHGMkG aj XdGd GdeLO hGQcH Edi GdHPd LhGO GdLO s
(3BNQgG (B:s
(3eKdc eKGd LeGdg eG Ndb eKdg hjNdb hgPG eG LeYJg ef ZRd GHf GdfHjg, hMPaJ GdeOM EP dG MGLI Hg s
(3TYQ hfKQ, dGHf ecGfS, hGHf fHGJI, hGHf GdeYJR, hJaj GdOjf Hf MLI, hGHf SfGA Gdedc, hGHf GdfHjg (B"(3aj GdZRd(B"(3,hQSGdI GdCRgGQ dVjGA GdOjf Hf GdCKjQ hQSGdI GdSja hGdbde dRjf GdOjf YeQ Hf GdhQOj hZjQge s
(3bQf GdfSN (B:s
(3GdbQf GdMGOj YTQs
(3JHUQI GdYfhGf (B:s
(3LeY s
(3GdJhKjbGJ GdeQLYjI (B:s
Keywords: (3GdCOHs